Non-physician anaesthesia providers’ perspectives on task sharing practices in Zambia and Somaliland: a qualitative study - Karydi, KI; Kabaghe, S; Blamey, H; Mohamed, M; Shamambo, N; Edgcombe, H (BMJ Publishing Group, 2024)
Introduction: The 68th World Health Assembly, in 2015, called for surgical and anaesthesia services strengthening. Acknowledging the healthcare staff shortages, they referred to task sharing, among others, as a more effective use of the healthcare workforce. While task sharing has been increasingly proposed as an important strategy to increase the reach and safety of anaesthesia as well as a means of supporting the workforce in low-resource settings, most data on task sharing relate to non-anaesthetic healthcare contexts. The aim of this study was to understand anaesthetic task sharing as currently experienced and/or envisaged by non-physician anaesthesia providers in Zambia and Somaliland. Methods: An exploratory qualitative research methodology was used. Participants were recruited initially via contacts of the research team, then through snowballing using a purposive sampling strategy. There were 13 participants: 7 from Somaliland and 6 from Zambia. Semistructured interviews took place synchronously, then were recorded, anonymised, transcribed and analysed thematically. Triangulation and respondents’ validation were used to maximise data validity. Results: Four major themes were identified in relation to task sharing practices: (1) participants recognised variable components of task sharing in their practice; (2) access to task sharing depends both on sources and resources; (3) implicit barriers may inhibit task sharing practices; (4) there is an appetite among participants for amelioration of current task sharing practices. Conclusions: Empowering task sharing practices can be achieved only by understanding how these practices work, by identifying gaps and areas of improvement, and by addressing them. The findings from this exploratory study could help the global community understand how anaesthetic task sharing in low-resource settings works and inspire further research on the field. This could inform future modelling of workforce planning strategies in low-resource settings to maximise the effectiveness and professional well-being of the workforce.